IMPLEMENTATION OF THE SAM'IYAH WA SYAFAWIYAH METHOD IN TEACHING ARABIC IN CLASS II OF MADRASAH TSANAWIYAH (MTs) PUTRA Al-ISHLAHUDDINY KEDIRI WEST LOMBOK - Moh. Zarkani (LPPM Universitas Kahuripan Kediri, 2023)
This research seeks to analyze the implementation of the Saam`iyah wa Syafawiyah method in teaching Arabic in class II of Madrasah Tsanawiyah Putra Al-Ishlahuddiny Kediri, West Lombok. The research method used is a qualitative filed research method using a qualitative descriptive approach and using a narrative qualitative strategy to try to investigate and tell the experience of the research object and retold by the researcher in narrative form. The results of the research show that the implementation of the Sam'iyah wa Syafawiyah method in teaching Arabic in Class II MTs Putra Al-Ishlahuddiny Kediri relies on the theory of the Sam'iyah wa Syafawiyah (Audio Lingual) method. However, regarding the implementation of the Sam'iyah wa Syafawiyahd Method in teaching Arabic in class II MTs Putra Al–Ishlahuddiny Kediri, it has run smoothly and is in accordance with what is stated in the theory of the Sam'iyah wa Syafawiyah Method, although it still requires improvement because there are several obstacles.